Are We Adequately Promoting Climate Change Adaptation to Address the Increasing Heatwaves Affecting the Elderly? - Alison Hutton; Kim Maud; Helen Giggins; Michela Skipp; Danielle Verdon-Kidd (International Journal of Disaster Risk Science)
Abstract Australia is a significant hotspot for heatwaves due to its geographical location and pronounced climatic variability, and heatwave exposure is expected to further increase in the future with anthropogenic climate change. With the intent to support United Nations Sustainable Development Goals 3 (Good health and well-being) and 13 (Climate action), in this study we identified key challenges and opportunities for adapting to heatwaves, focusing on the most vulnerable members of our community—older adults. A naturalistic, qualitative approach was selected for this study. Data were collected via semistructured interviews. Key insights were captured through a series of semistructured interviews with key informants from local government agencies and community groups that provide care for older adults in New South Wales, Australia. Questions centered around current preventative measures adopted by the organization regarding heatwaves, level of heatwave knowledge of local residents, and common effects of heatwaves in the local community. The findings highlight four primary challenges: (1) increasing duration and intensity of heatwaves; (2) lack of knowledge among older adults regarding symptoms and the effect on the body; (3) the financial and social impacts of heatwaves; and (4) inadequate urban planning practices and building codes including the need for the creation of cool and green spaces. This study provides important insights for protecting our most vulnerable populations from the growing threat of heatwaves.